Pemanfaatan ampas tahu dan eceng gondok sebagai pakan lele pada kolam terpal di Dusun I Desa Lubuk Siam Kecamatan Siak Hulu Kabupaten Kampar, Riau - Efawani Efawani; Tengku Dahril; Ridwan Manda Putra; Deni Efizon; Yuliati Yuliati; Rivco Hastwoyundra (Unri Conference Series: Community Engagement, 2019)
The activities of this community about the utilization of tofu dregs and water hyacinth as catfish feed in tarpaulin ponds that have been done in Lubuk Siam Village, Siak Hulu Sub-District, Kampar Regency, Riau, the form of public awareness and training. The purpose of this activity is to providing knowledge and application of techniques about making feed catfish from the tofu dregs and water hyacinth are fermented with the EM4 for catfish farming in tarpaulin ponds. On the implementation of this extension and training activities using methods lectures, discussions and demonstrations. The target fish farmers/partners and the community on Hamlet I in Lubuk Siam Village. Results and achievement of targets have provided solutions to overcome the problem of catfish feed costs and the length of the production/harvest period (± 6 months) in the cultivation business it does to ± 3.5 months by minimizing feed costs from Rp.17,000-Rp.20,000/kg to Rp.3,000-Rp.5,000/kg, so you can save on fish feed costs by 50-60%. This Community Service activity received a positive response from the Village Head and village officials and the people of Lubuk Siam Village. Efforts to empower the community of Lubuk Siam Village, it can be seen that the partners have succeeded in making their own feed, adding to the partner's income for a pool measuring 10 m x 16 m with a dense thickness of 25,000-30,000 head of Rp.3,000,000-Rp.4,000,000/month and can improve family nutrition.